Analisis Pengaruh Job Stress, Work-Life Balance, dan Dukungan Organisasi terhadap Burnout pada karyawan: Sebuah Systematic Literature Review - Nasr, Faidh Rahmani (Jurnal Manajemen dan Budaya, 2026)
This study aims to analyze the relationship between job stress, organizational support, and work-life balance on employee burnout using a Systematic Literature Review (SLR) approach. The literature selection process was conducted through databases such as Google Scholar, ScienceDirect, and Taylor & Francis Online using the keywords “job stress,” “organizational support,” “work-life balance,” and “burnout.” The synthesis results indicate that most studies identify job stress as the primary factor contributing to burnout, particularly in the healthcare, education, and hospitality sectors, which are characterized by high work intensity. Organizational support in the form of empathetic leadership, effective communication, and recognition of employee performance has been proven to enhance resilience and reduce emotional exhaustion. Meanwhile, organizational policies that promote work-life balance—such as flexible working hours, hybrid work systems, as well as humane leave and employee well-being programs—are among the most effective strategies for reducing burnout levels. These findings emphasize that burnout is not merely the result of individual pressure but also a consequence of organizational policies that fail to adapt to employees’ psychological needs. Therefore, companies need to integrate flexible work arrangements, empathetic supervisory support, and psychological well-being programs to foster a healthy, productive, and sustainable work environment.